Epigenome-wide association of myocardial infarction with DNA methylation sites at loci related to cardiovascular disease - Masahiro Nakatochi; Sahoko Ichihara; Ken Yamamoto; Keiko Naruse; Shigeki Yokota; Hiroyuki Asano; Tatsuaki Matsubara; Mitsuhiro Yokota (Clinical Epigenetics, 2017)
Abstract Background Development of cardiovascular disease (CVD), including coronary artery disease, arrhythmia, and ischemic stroke, depends on environmental and genetic factors. To investigate the epigenetic basis of myocardial infarction (MI), we performed an epigenome-wide association study for this condition in elderly Japanese subjects. A total of 192 case subjects with MI and 192 control subjects were recruited from hospital attendees and the general population, respectively. Genome-wide DNA methylation (DNAm) profiles for DNA isolated from whole blood were obtained by analysis with an Infinium HumanMethylation450 BeadChip. The relation of DNAm sites found to be significantly associated with MI to nearby single nucleotide polymorphisms (SNPs) previously shown to be associated with CVD was assessed in the control group. Findings Three DNAm sites (cg06642177, cg07786668, cg17218495) showed genome-wide significant associations with MI (p = 4.33 × 10−8, 3.96 × 10−10, and 3.77 × 10−8, respectively). Two of these sites (cg07786668, cg17218495) still showed such associations after adjustment for classical risk factors of MI (p = 1.04 × 10−7 and 6.60 × 10−8, respectively). The DNAm sites cg07786668 and cg17218495 are located in ZFHX3 (zinc finger homeobox 3) and SMARCA4 (SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily a, member 4) genes, respectively. SNPs in ZFHX3 or SMARCA4 that were previously found to be associated with CVD were not significantly associated with these DNAm sites in our control subjects. Conclusions We identified two DNAm sites—cg07786668 in ZFHX3 and cg17218495 in SMARCA4— that are independently and significantly associated with MI. Our results suggest that the development of MI might be influenced by changes in DNAm at these sites via a pathway that differs from that affected by CVD-associated SNPs in these genes. The Kita-Nagoya Genomic Epidemiology (KING) study, which was the source of control samples in the present study, was registered in ClinicalTrials.gov (NCT00262691) on 6 December 2005.